“Making families”: parenting and belonging in transnational adoption in Flanders - De Graeve, Katrien (Afrika Focus, 2012)
The goal of this PhD project is to address major gaps in the present research by providing a theoretical and empirically-informed account of the narratives and performances of transnational adoptive parents. By exploring how adoptive parents both normalize and problematize the perceived differences of their children and families, and by examining what work is done and which imaginations are drawn upon in relation to that difference, it aims to gain insight into how racial, cultural and genetic diversity is metabolized within the so-called private realm of the family. Based within a feminist and constructivist anthropological epistemology, this thesis explores the identity work that parents conduct both for themselves, and on behalf of their children, and examines the citizenship potential of adoptive parents’ parenting work.